2017
DOI: 10.2474/trol.12.155
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication Mechanism of Halogen-Free Ionic Liquids

Abstract: Ionic liquids have potential for use as novel high-performance lubricants because of their attractive characteristics such as low volatility, high-thermal stability, and oxidation stability. It is known that ionic liquids exhibit excellent lubricity for metals because of halogen constituents in their molecular structure. However, occurrence of corrosive damage on the contacting surfaces lubricated with the ionic liquids has also been reported. To prevent damage due to corrosion, it is necessary to use halogen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In this study, the reduction in friction between steel disks lubricated with (BMIM)(DCN) and (BMIM)(TCC) was confirmed at 90 • C and 170 • C, respectively. With regard to the friction reduction mechanism of DLC, graphitization of DLC at the friction interface has been pointed out as the cause [31][32][33][34][35][36]. The results of Raman spectroscopy indicated that the graphitization of the ta-C film progressed on the worn surface at the temperature corresponding to the low friction coefficient, which affected the friction behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the reduction in friction between steel disks lubricated with (BMIM)(DCN) and (BMIM)(TCC) was confirmed at 90 • C and 170 • C, respectively. With regard to the friction reduction mechanism of DLC, graphitization of DLC at the friction interface has been pointed out as the cause [31][32][33][34][35][36]. The results of Raman spectroscopy indicated that the graphitization of the ta-C film progressed on the worn surface at the temperature corresponding to the low friction coefficient, which affected the friction behavior.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-TOF/MS analyses indicated that the anions from the ionic liquid adsorbed on the worn surface at the temperature corresponding to the low friction coefficient. The presence of anions on the worn surface and the reduction in friction due to the adsorbed anions have often been reported [19,20,32,37,38]. It has been reported that the ta-C film surface is reactive due to the presence of dangling bonds and reacts with the lubricants [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the specific wear rate of halogen-free ionic liquids is very large even with low friction (Kawada et al, 2018b). Another effective means is to use sliding materials made of hard materials (Kawada et al, 2017a), (Kondo et al, 2013). Ceramics, nitrogen coating, and diamond-like carbon (DLC) improve the tribological performances of halogen-free ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, tetrafluoroborate and hexafluorophosphate undergo hydrolysis when exposed to moisture and generate hydrogen fluoride even without sliding [25][26][27]. To prevent corrosion, use of fluorinefree ionic liquids, such as bis(oxalato)borate, ethylsulfate, diethylphosphate, dicyandiamide, tricyanomethane, and tetracyanoborate has been explored [28][29][30][31][32][33]. These ionic liquids do not have fluorine in their chemical strucutres, and therefore, they have a low risk of corrosion damage.…”
Section: Introductionmentioning
confidence: 99%